2018
DOI: 10.3390/machines6020012
|View full text |Cite
|
Sign up to set email alerts
|

System Identification Algorithm for Computing the Modal Parameters of Linear Mechanical Systems

Abstract: Abstract:The goal of this investigation is to construct a computational procedure for identifying the modal parameters of linear mechanical systems. The methodology employed in the paper is based on the Eigensystem Realization Algorithm implemented in conjunction with the Observer/Kalman Filter Identification method (ERA/OKID). This method represents an effective and efficient system identification numerical procedure based on the time domain. The algorithm developed in this work is tested by means of numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…At this point, several simulations of the deployment phase have been carried out to find the spring stiffness and damping coefficient of the dampers, imposing an opening time of the mechanism of about 30 s as a constraint. The integration method and the values of the parameters used for the simulation have been adapted for the specific case of contacts as suggested in References [23][24][25][26]. The selection of the stiffnesses of the torsion springs was influenced by the maximum torsion angle, which must be greater than 177 • , and by the diameter of the pin (8 mm) on which the spring is to be positioned.…”
Section: Spring-damper Systemmentioning
confidence: 99%
“…At this point, several simulations of the deployment phase have been carried out to find the spring stiffness and damping coefficient of the dampers, imposing an opening time of the mechanism of about 30 s as a constraint. The integration method and the values of the parameters used for the simulation have been adapted for the specific case of contacts as suggested in References [23][24][25][26]. The selection of the stiffnesses of the torsion springs was influenced by the maximum torsion angle, which must be greater than 177 • , and by the diameter of the pin (8 mm) on which the spring is to be positioned.…”
Section: Spring-damper Systemmentioning
confidence: 99%
“…To date, a number of vibration-based system identification and damage detection methods have been developed, and review articles with different emphases can be also found [2][3][4]. In general, structural parameters identification can be performed in three different paradigms: (i) time domain (e.g., [5][6][7][8][9][10]), (ii) frequency domain (e.g., [11][12][13][14]), and (iii) time-frequency domain (e.g., [15][16][17]).…”
Section: Literature Surveymentioning
confidence: 99%
“…As it is known, the wood has a behavior orthotropic and therefore it is necessary to evaluate the different characteristic moduli for these types of materials, for which it is necessary to use mathematical models more complex to simulate its behaviour. We will refer to the theory of the orthotropic plates broadly treated in the literature [37][38][39][40].…”
mentioning
confidence: 99%